Metode demonstrasi pada pembelajaran jarak jauh mata pelajaran gambar teknik di Sekolah Menengah Kejuruan - M. Agphin Ramadhan; Arris Maulana; Ana Amalia Islami; Muhammad Rijal Basyir; Valiant Lukad Perdana Sutrisno (University of Muhammadiyah Malang, 2022)
The existence of the Covid-19 pandemic is a challenge for learning in vocational schools, especially in practical learning. In the Vocational School of Design, Modeling, and Building Information (DPIB), a Technical Drawing subject aims to prepare students to be skilled at drawing building construction. This research is a Classroom Action Research that aims to determine changes in the learning outcomes of class X students of DPIB skill competence using the demonstration method. This research was conducted in 3 stages: pre-cycle, Cycle I, and Cycle 2. The data analysis showed that at the pre-cycle stage, student learning outcomes only had an average score of 68.653, and 26 of 32 students completed learning. Next, student learning outcomes in the first cycle experienced a relatively high increase of 11%, with an average score of 80.4, with 28 students completed carrying out learning. Then, the test was continued in cycle II with several improvements. At this stage, student learning outcomes increased by 4% from cycle I, with an average score of 84, and 28 students completed learning. The demonstration method is proven effective in applying to Engineering Drawing subjects that are carried out remotely because it can improve student learning outcomes.